Sistematização da crítica de Skinner à cultura contemporânea ocidental - Caro, Daniel de Moraes (2013)
The present work consists of a systematization of Skinner criticism to contemporary Ocidental culture. Two operations characterize this systematization: one of organization and the next, on the fundamentation of Skinner s nine texts about criticism of this culture. In order to point the way towards the field of studies this work (culture) was approached by Skinner, the first chapter was built in order to characterize the philosophical presuppositions of radical behaviorism. This chapter indicated the philosophical demands of culture should be addressed. Then, in the second chapter, the notion of culture in the work of Skinner was explored. Two concepts have proved important for understanding the concept of culture: social behavior and verbal behavior. Both received a specific approach each one on an item. Moreover, in the same chapter, deepened further the concept of culture unraveling the relationship between culture and subjectivity. The chapter ended with a discussion about a possible notion of "critic" that could be applied at cultural practices. Critic to a cultural practice would be legitimate, the definition of "critic" adopted in the present work, when such practice would produce threat to the survival of the culture. Based on this criterion, we identified cultural practices analyzed in the nine texts that could be considered under criticism from Skinner. These practices were grouped into thematic units that were the basic methodological feature that helped in the task of systematic criticism of Skinner to contemporary Western culture. Four thematic units were formed: internalization of the main determinants of behavior, neglect of the remote future, impoverishment of behavioral repertoire and dissemination of aversive control. It was observed in the present analysis in thematic units, a strong commitment of Skinner's critic with its conceptual and philosophical system